Cancer Survivorship and Subclinical Myocardial Damage: The ARIC Study. Issue 12 (30th March 2019) - Florido, Roberta; Lee, Alexandra K; McEvoy, John W; Hoogeveen, Ron C; Koton, Silvia; Vitolins, Mara Z; Shenoy, Chetan; Russell, Stuart D; Blumenthal, Roger S; Ndumele, Chiadi E; Ballantyne, Christie M; Joshu, Corinne E; et al.
Abstract: Cancer survivors might have an excess risk of cardiovascular disease (CVD) resulting from toxicities of cancer therapies and a high burden of CVD risk factors. We sought to evaluate the association of cancer survivorship with subclinical myocardial damage, as assessed by elevated high-sensitivity cardiac troponin T (hs-cTnT) test results. We included 3, 512 participants of the Atherosclerosis Risk in Communities Study who attended visit 5 (2011–2013) and were free of CVD (coronary heart disease, heart failure, or stroke). We used multivariate logistic regression to evaluate the cross-sectional associations of survivorship from any, non-sex-related, and sex-related cancers (e.g., breast, prostate) with elevated hs-cTnT (≥14 ng/L). Of 3, 512 participants (mean age, 76 years; 62% women; 21% black), 19% were cancer survivors. Cancer survivors had significantly higher odds of elevated hs-cTnT (OR = 1.26, 95% CI: 1.03, 1.53). Results were similar for survivors of non-sex-related and colorectal cancers, but there was no association between survivorship from breast and prostate cancers and elevated hs-cTnT. Results were similar after additional adjustments for CVD risk factors. Survivors of some cancers might be more likely to have elevated hs-cTnT than persons without prior cancer. The excess burden of subclinical myocardial damage in this population might not be fully explained by traditional CVD risk factors.